Enhancing nursing students' understanding of threshold concepts through the use of digital stories and a virtual community called 'Wiimali'. Issue 2 (March 2015) - Levett-Jones, Tracy; Bowen, Lynette; Morris, Amanda
Abstract: Wiimali is a dynamic virtual community developed in 2010 and first implemented into our Bachelor of Nursing (BN) program in 2011. The word Wiimali comes from the Gumiluraai Aboriginal language. Wiimali and the digital stories it comprises were designed to engage nursing students and enhance their understanding of the threshold concepts integral to safe and effective nursing practice. In this paper we illustrate some of the key features of Wiimali with web links to a virtual tour of the community and a selection of digital stories. We explain how this innovative educational approach has the potential to lead to transformative learning about concepts such as social justice, person-centred care and patient safety. Consistent feedback about Wiimali attests to the positive impact of this educational approach. Students have commented on how Wiimali caused them to think differently about the concepts of community and social justice; how it brings the health-related problems of community members to life; and how the digital stories enhance their learning about person-centred care and patient safety. Highlights: Wiimali immerses facilitates professional transformation, and challenges students to 'think like a nurse'. Virtual communities create a sense of authenticity and allow for engagement with community members and health professionals. Digital stories provide learners with a powerful and effective way to learn, remember and reflect. Learners presented with a story linked to a series of facts retain significantly more than those presented with facts alone.